2019
DOI: 10.1038/s41598-019-48143-y
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Soot Compaction by Cloud Processing from Laboratory and Field Observations

Abstract: Soot particles form during combustion of carbonaceous materials and impact climate and air quality. When freshly emitted, they are typically fractal-like aggregates. After atmospheric aging, they can act as cloud condensation nuclei, and water condensation or evaporation restructure them to more compact aggregates, affecting their optical, aerodynamic, and surface properties. Here we survey the morphology of ambient soot particles from various locations and different environmental and aging conditions. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 83 publications
5
55
1
Order By: Relevance
“…The difference in particle morphology is consistent with the findings of China et al. (), reporting higher roundness for soot particles from ice crystal residuals, as compared to nascent soot aggregates and also with the more recent findings of Bhandari et al (), who report strong compaction of soot particles upon cloud processing. In such soot aggregates, ice nucleation through PCF is more likely to take place due to the increase in available pore water and reduction of interpore spacing (David et al., ) and the higher overall spatial density of pores, enhancing the probability of pores with the right characteristics (size and contact angle) to be available for condensation of water and subsequent homogeneous freezing within the pore.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The difference in particle morphology is consistent with the findings of China et al. (), reporting higher roundness for soot particles from ice crystal residuals, as compared to nascent soot aggregates and also with the more recent findings of Bhandari et al (), who report strong compaction of soot particles upon cloud processing. In such soot aggregates, ice nucleation through PCF is more likely to take place due to the increase in available pore water and reduction of interpore spacing (David et al., ) and the higher overall spatial density of pores, enhancing the probability of pores with the right characteristics (size and contact angle) to be available for condensation of water and subsequent homogeneous freezing within the pore.…”
Section: Resultssupporting
confidence: 91%
“…In fact, China et al. () and more recently Bhandari et al () have reported strongly compacted soot particles to be long range transported within the free troposphere. Moreover, scavenging of soot particles by cloud droplets was recently found to lead to large, compacted aggregates, that can be released back into the atmosphere in MPC conditions, when the cloud droplets evaporate at the expense of growing ice crystals (Ding et al., ).…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in pore water available to initiate ice formation via PCF can emanate from both physical and chemical changes of the aerosol and specically pore properties upon aging. 32 The aging in aqueous solutions likely caused a restructuring in the soot particle morphology, similar to the compaction of soot particles observed during cloud processing in other studies, 27,86 that can contribute to an overall increase in the number of mesopores present and hence mesopore volume. At the same time, lowering the soot-water contact angle of the pores present could increase the mesopore volume accessible for water to condense at a lower RH w (compared to unaged soot) and hence PCF to occur even in the absence of any morphological change.…”
Section: Aged Mcastblmentioning
confidence: 56%